1978
DOI: 10.1002/1097-0142(197805)41:5<1845::aid-cncr2820410528>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytology and colchicine sensitivity of viable cells from lymph nodes with malignant lymphoma

Abstract: Viable cell suspensions were prepared from 31 nodes diagnosed non-Hodgkin's malignant lymphoma, and from 30 non-malignant nodes. The cells were examined and counted by phase contrast microscopy. The suspensions were characterized by the percentage of large cells and by a colchicine-sensitivity index.The finding of more than 6% large cells or the finding of a sensitivity index of more than 30% was considered a positive test for a malignant lymphoma.According to these criteria there were 2 false positives in 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The presence of a high proportion of CUS cells in 77% of tissue biopsy samples from 30 patients with NHDL is a similar result to that found by Schrek et al (1978). They reported that 22 (85%) of 26 lymphnode specimens showed CUS, but only 1/22 reactive nodes studied as controls.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The presence of a high proportion of CUS cells in 77% of tissue biopsy samples from 30 patients with NHDL is a similar result to that found by Schrek et al (1978). They reported that 22 (85%) of 26 lymphnode specimens showed CUS, but only 1/22 reactive nodes studied as controls.…”
Section: Discussionsupporting
confidence: 81%
“…A "nucleus-associated tubulincontaining structure" was found in virtually all lymphocytes from normal subjects, but in a considerably lower number of CLL lymphocytes (Dighiero et al, 1978). This hypothesis of the mode of action of colchicine, however, does not explain the finding that the ionophore A23187, which causes uptake into the cell of calcium and other divalent ions, induces resistance to colchicine and vincristine (Schrek et al, 1978).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations